Photocatalytic Decomposition of Amoxicillin Trihydrate Antibiotic in Aqueous Solutions under UV Irradiation Using Sn/TiO2 Nanoparticles - Robab Mohammadi; Bakhshali Massoumi; Mohammad Rabani (International Journal of Photoenergy)
TiO2 and Sn/TiO2 nanoparticles were successfully synthesized by sol-gel method. The resulting nanoparticles were characterized by XRD, TEM, SEM, UV-Vis reflectance spectroscopy, and BET analysis methods. The effects of Sn-doping on the crystal structure, surface area, adsorption properties, pore size distribution, and optical absorption properties of the catalysts were investigated. The effect of different Sn content on the amount of hydroxyl radical was discussed by using salicylic acid as probe molecule. The photocatalytic activity of samples was tested by photocatalytic mineralization of amoxicillin trihydrate (AMOX) as a model pollutant. Sn/TiO2 nanoparticles exhibited high photocatalytic activity during the mineralization of AMOX under UV light due to increase in the generated hydroxyl radicals, band gap energy, specific surface area, and decrease in the crystallite size. The kinetic of the mineralization of AMOX can be explained in terms of the Langmuir-Hinshelwood model. The values of the adsorption equilibrium constant (𝐾AMOX) and the kinetic rate constant of surface reaction (𝑘c) were 0.56 (mg L−1)−1 and 1.86 mg L−1 min−1, respectively.